The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1365-2966.2012.20591.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of candidate Be stars in the Magellanic Clouds using near-infrared photometry and optical spectroscopy

Abstract: Mennickent et al. and Sabogal et al. identified a large number of classical Be (CBe) candidates (∼3500) in the Large and Small Magellanic Clouds (LMC and SMC) based on their photometric variability using the OGLE II data base. They classified these stars into four different groups based on the appearance of their variability. In order to refine and understand the nature of this large number of stars, we studied the infrared properties of the sample and the spectroscopic properties of a subsample. We cross‐corr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 27 publications
5
17
1
1
Order By: Relevance
“…Subsequently, we estimated the emission strength ratio of Ca 8498:8542:8662 Å lines is 1:1:1 for nine cases which is quite different from the theoretically predicted value of 1:9:5 (Osterbrock & Ferland 2006;Polidan & Peters 1976). The theoretically predicted emission strength ratio 1:9:5 corresponds to an optically thin scenario whereas a deviation from this considers the line forming region as optically thick.…”
Section: Subtracting the Ca Emission Components From The Correspondincontrasting
confidence: 69%
“…Subsequently, we estimated the emission strength ratio of Ca 8498:8542:8662 Å lines is 1:1:1 for nine cases which is quite different from the theoretically predicted value of 1:9:5 (Osterbrock & Ferland 2006;Polidan & Peters 1976). The theoretically predicted emission strength ratio 1:9:5 corresponds to an optically thin scenario whereas a deviation from this considers the line forming region as optically thick.…”
Section: Subtracting the Ca Emission Components From The Correspondincontrasting
confidence: 69%
“…Since SPM4 measured a V magnitude, a comparison with their OGLE-II's V could provide additional information to clarify these problematic matches and also to discard false matches, but the SPM4 photometry in the LMC and SMC areas comes mostly from photographic plates and has a poor quality compared to CCD photometry. We also noticed the J-H vs. H-K color-color diagram done with the JHKs 2MASS magnitudes listed by SPM4, suffered from a noticeable higher dispersion, as compared to those published by Paul et al (2012) using the InfraRed Survey Facility (IRSF) magnitudes by Kato et al (2007).…”
Section: Cross-matching Be Stars With Irsf and Spm4supporting
confidence: 56%
“…This last hypothesis was discarded in the study by Mennickent et al (2009). Paul et al (2012) showed that the photometric method used in the aforementioned works is effective in the selection of Be star candidates. Their spectroscopic analysis found that most of the stars studied from a sample of such candidates in both LMC and SMC, belong to early type stars with emission supporting circumstellar material.…”
Section: Introductionmentioning
confidence: 99%
“…There have also been detections of a number of bona fide Be and metal-weak stars (compared to the metallicity of the SMC). Three of those detections were already known as Be stars (Paul et al 2012), thereby constituting a valuable test for the reliability of our observations.…”
Section: Results and Outlookmentioning
confidence: 83%